Biological characterization, expression, and functional analysis of tumor necrosis factor receptor-associated factor 6 in Nile tilapia (Oreochromis niloticus). Issue 80 (September 2018) - Wang, Zhiwen; Huang, Yu; Li, Yuan; Wang, Bei; Lu, Yishan; Xia, Liqun; Tang, Jufen; Jian, JiChang
Abstract: Nile tilapia ( Oreochromis niloticus ) is a pivotal economic fish that has been plagued by Streptococcus agalactiae infections for many years. Tumor necrosis factor receptor-associated factor 6 (TRAF6) is a crucial adaptor molecule of the interleukin-1 receptor/Toll-like receptor (IL-1/TLR) superfamily, which can trigger downstream signaling cascades involved in innate immunity. In this study, the full-length cDNA of TRAF6 was cloned from O. niloticus (named On-TRAF6 ), which has an open reading frame of 1716 bp, and encode a polypeptide of 571 amino acids. The predicted amino acid sequence of On-TRAF6 contained the characteristic motifs of TRAF proteins, including a Zinc finger of RING-type, two Zinc fingers of TRAF-type, and a MATH (meprin and TRAF homology) domain. Multiple sequence alignment revealed that On-TRAF6 shares a relatively high level of identity with those of other fishes (64–98%). In healthy tilapia, mRNA expression of On-TRAF6 could be detected in all the examined tissues and the highest expression occurred in the spleen. Moreover, we found that On-TRAF6 was involved immune response of Nile tilapia following the stimulation with Streptococcus agalactiae and polyinosinic: polycytidylic acid (Poly I:C) when determined by using qPCR. The result of subcellular localization showed that On-TRAF6 distributed in the cytoplasm, and over-expression of On-TRAF6 could strongly activated NF-кB pathway in HEK293T cells. These findings indicated that On-TRAF6 may play an important role in the immune response to intracellular bacteria in Nile tilapia. Highlights: Homologue of On-TRAF6 was identified from Nile tilapia, Oreochromis niloticus. On-TRAF6 was significantly up-regulated in response to Streptococcus agalactiae and Poly I:C stimulus. Over-expression of On-TRAF6 could strongly activated NF-кB pathway in HEK293T cells.